Respon Pupuk Kandang Ayam dan Pupuk NPK 20-20-20 Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Laia, Sadarman; Harahap, Rahmaniah; Dewi, Dora Silvia (JURNAL AGROPLASMA, 2026)
Pakcoy (Brassica rapa L.) is a leafy vegetable with high nutritional value widely consumed in Indonesia. However, its productivity in the field is often limited by inadequate macro and micronutrient availability in the soil. Balanced fertilization using both organic and inorganic sources is crucial to support optimal growth and yield. This study aimed to determine the effects of chicken manure and NPK 20-20-20 fertilizer, both individually and in combination, on the growth and yield of pakcoy plants. The research was conducted over two months (June–August) at the experimental field of the University of Community Development using a factorial Randomized Complete Block Design (RCBD) with two factors: chicken manure (0, 1, 2, and 3 kg/plot) and NPK 20-20-20 fertilizer (0, 15, 20, and 25 g/plot), each with three replications. Observed parameters included plant height, number of leaves, shoot fresh weight, and root length. The results showed that chicken manure significantly affected plant height (weeks 1 and 4) and shoot fresh weight. The K2 treatment (2 kg/plot) produced the highest results with a plant height of 41.2 cm and a fresh weight of 118.1 g. NPK fertilizer alone had limited effect, but N1 (15 g/plot) yielded the longest root (28.9 cm) and the highest shoot fresh weight (128.5 g). The interaction between the two fertilizers was significant, with the K2N1 combination producing the highest shoot weight (203.0 g), and K1N1 yielding the longest root (40.1 cm). In conclusion, the combination of 2 kg/plot chicken manure and 15 g/plot NPK fertilizer is the most effective treatment to enhance pakcoy growth and yield. Moderate doses of organic and inorganic fertilizers are proven to support sustainable pakcoy cultivation. Keywords: chicken manure, growth, NPK 20-20-20, pakcoy, yield